ANALISIS PENGENDALIAN KUALITAS DENGAN PENDEKATAN P.D.C.A. (PLAN-DO-CHECK-ACT) BERDASARKAN STANDAR MINIMAL PELAYANAN RUMAH SAKIT PADA RSUD Dr. ADHYATMA SEMARANG (STUDI KASUS PADA INSTALASI RADIOLOGI) - Dewi, Ariani Puspita; Nugraha, Hari Susanta; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2014)
good quality health care is health care that can satisfy every user services. One of the activities in order to create quality standards is to implement appropriate quality control system, have clear objectives and stages, as well as providing innovation in the prevention and resolution of problems faced by the hospital, according to the Ministry of Health Decree No. 129/Menkes/SK/II/2008 on hospital minimum service standards. This research studies about the quality control process of Radiology Department in Dr. Adhyatma Public Hospital Semarang by using the approach of P.D.C.A. cycle (Plan-Do-Check-Act), based on a minimum standard of hospital services. Based on analysis, it was found that the overall service quality control has been going well. But there is still a level of damage x-rays that are above the standard which more than (>) 2%, so it’s need an improvement of the quality of x-rays to be able to provide high quality x-rays in order to create the right diagnosis and provide a satisfactory health care for patients of Radiology Department in Dr. Adhyatma Public Hospital Semarang.